Los Materiales Didácticos y el aprendizaje de la matemática - Oscco Solórzano, Rolando (2019)
Teaching materials have always been strictly necessary in the teaching of any discipline. They are a valuable tool to make the act of understanding more viable by the student, since when we talk about teaching, in fact we are also referring to learning, an issue that lately is taking the importance it deserves. These materials are applicable to any discipline or branch of knowledge, but in the area of ​​factual sciences they present some distinctive features, such as visualizing an abstract fact and knowing its usefulness in the explanation through the material. Many authors also used the term Teaching Medium, although it is somewhat more generalizing. The following work was based on an application-based investigation whose objective was to determine the relationship between the teaching materials and the academic performance of the students of Higher Education who choose to be Mathematics teachers. The sample consisted of 20 students from the first cycle of the Primary Education professional career, and from the instruments applied the results were collected, which, when taking the most significant, served as the basis for the conclusions offered at the end.